Growth, Composition and Direction of Nepalese Foreign Trade - Pokharel, Suman; Kandangwa, Tulasi Kumar (KMC Research Journal, 2024)
This article explores the growth, composition, and direction of foreign trade in Nepal, a landlocked country heavily reliant on international trade for its economic development. The study analyzes a ten-year period from 2012/13 to 2021/22 using secondary data from the Ministry of Finance and Nepal Rastra Bank. The findings reveal a significant increase in Nepal’s trade volume, exports, and imports during this period; however, the growth rate of imports surpasses that of exports, leading to a persistent trade deficit. The composition of foreign trade is examined, highlighting the major commodity groups and export items. To achieve the objective of the research, a Qualitative Research Methodology and a Descriptive Approach has been employed. The analysis showcases the changing dynamics and fluctuations in export patterns across various sectors. Furthermore, the study investigates the direction of Nepal’s foreign trade, emphasizing the growing reliance on imports from India. The article underscores the need to enhance export-oriented industries and promote import substitution to address the trade imbalance. Overall, the research contributes valuable insights for policymakers, businesses, and stakeholders to formulate effective strategies and enhance Nepal’s trade competitiveness.